Strengthening Family Foundations:A Study of Prophet’s Biography - jamal farzand vahi; leyla kuhi (پژوهش نامه معارف قرآنی, 2012)
This study uses library research methodology to investigate how to strengthen the family ties using the Prophet’s life as a model. Emphasizing the critical position of families, this paper seeks to enumerate goals of family formation aimed at meeting the material, spiritual and mental needs of human beings including their need for peace and security. As stated in this study, to reach the sublime goals and objectives of Islam and to protect and maintain their very existence one needs to seriously take care of the family law as stipulated in Islam. It is therefore necessary that all the plans and policy makings be in line with the promotion and interest of the institution of family, and meanwhile the job and occupation of family members should be clearly defined and provided for. Finally, this paper clarifies the role of the holy motivations behind occupation of the family members and reviews the life of the Prophet (pbuh) and his living expenses through religious literature. The above are only few of the many internal and external factors in family relations which can be implemented using the life of the prophets and especially the Prophet of Islam and the Infallible Imams as the model in life.